Differential strain transfer, Longmen Shan thrust belt, eastern Tibetan Plateau margin: Implications for seismic hazards. (January 2019) - Shao, Chongjian; Li, Yong; Yan, Zhaokun; Liu, Shao; Zhou, Rongjun; Li, Jingbo; Dong, Shunli; Yan, Liang; Deng, Tao; Nie, Zhou
Graphical abstract: Highlights: Strain transfer is mainly affected by thickness of shallow detachment. Seismic gap is ascribed to ductile rocks and enhanced strain transfer. Abstract: Southeastward strain transfer in the middle-southern Longmen Shan (LMS) thrust belt not only can promote the development of fault-related folds and earthquakes in the piedmont, but also affect the seismogenic capacity of the middle-southern LMS thrust belt. However, the detailed transfer process remains elusive. In this work, we combine structural profile re-analysis, sandbox modeling and seismic statistics to illustrate the strain transfer process. Our main results indicate that: (1) the thickness of the shallow detachment (e.g. Middle-Lower Triassic gypsum-salt strata) is probably the main factor for differences in southeastward strain transfer within the domain between the middle-southern LMS thrust belt and Weiyuan-Moxi anticline. This is also supported by our sandbox model; (2) the seismogenic capacity in the southern LMS thrust belt is probably proportional to the corresponding shortening of the Range Front Blind Thrust (RFBT). Thus, seismogenic capacity in the seismic gap zone is weaker than those of other segments of the southern LMS thrust belt, which is probably < Ms 7.0. (3) The weak seismogenic capacity (<Ms 7.0) and formation of the seismic gap is probably attributed to weak petrophysical properties and enhanced southeastward strain transfer. It is worth noting that the 1970 Dayi Ms 6.2 earthquake probably released most energy of the seismic gap. Further, this work also sheds light on the evaluation of seismic hazard in the LMS and other orogenic belts.